Gender and Media: A Critical Analysis of Nigeria's Media Landscape - Mary Eyiaro (Budapest International Research and Critics University, 2025)
Media in its diverse forms remains a powerful force in shaping public perception, social identities, and political discourse, making gender representation a central concern within communication research. This paper examines the construction of gender across African media, with particular focus on Nigeria’s media landscape. It interrogates how news reporting, advertising, entertainment content, and political communication reflect, reinforce, and at times contest traditional power relations between men and women. Drawing on illustrative cases such as the public controversy between Natasha Akpoti-Uduaghan and Godswill Akpabio, gendered advertising practices in Nigeria’s beverage industry, and recurring portrayals in Nollywood productions, the paper identifies persistent patterns of female objectification, marginalization in political narratives, and stereotypical characterization. The analysis further highlights structural inequalities embedded in media ownership, newsroom hierarchies, content production processes, and audience targeting strategies. The paper concludes that, despite emerging counter-narratives and digital activism challenging dominant frames, Nigerian media institutions largely reproduce patriarchal gender norms through agenda-setting and framing practices that privilege masculine authority and visibility.